Thyrotoxicosis after COVID-19 Infection with a Delay in Graves’ Disease Antibody Positivity - Dennis C. Boyle; Jamie A. Mullally (Case Reports in Endocrinology)
Background and Objective. Mounting evidence implicates COVID-19 as a cause of thyroid dysfunction, including thyrotoxicosis due to both thyroiditis and Graves’ disease (GD). In this report, we present a case of thyrotoxicosis following COVID-19 infection that was ultimately found to represent GD with significantly delayed diagnostic serum antibody positivity. Case Report. A 65-year-old woman with a history of uncomplicated COVID-19 infection one month prior, presented to the Emergency Department with exertional dyspnea and palpitations, and was found to be in atrial fibrillation with rapid ventricular response (AF with RVR). Labs showed subclinical hyperthyroidism and the patient was started on a beta-blocker and methimazole. One month later, thyroid-stimulating immunoglobulin (TSI) resulted negative and thyroid function tests had normalized. The clinical picture suggested thyroiditis, and methimazole was stopped. One month later, the patient again presented in AF with RVR, with labs showing overt biochemical thyrotoxicosis. Antibodies were re-tested, and the thyrotropin receptor antibody (TRAb) and TSI resulted positive, confirming GD. Discussion. Most notable in this case is the feature of delayed GD antibody positivity: the diagnostic immunoassay for GD resulted negative one and two months after infection, but was ultimately positive three months after infection. To the authors’ knowledge, this represents the longest delayed antibody positivity reported to date, amongst cases of new-onset GD following COVID. Conclusion. The clinical course of GD following COVID-19 infection is highly variable. This case underscores the need for vigilance in monitoring for delayed GD antibody positivity due to the important therapeutic implications of distinguishing thyroiditis from GD.